2013
DOI: 10.1097/mlr.0b013e3182a97b5d
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Out-of-Pocket Costs on the Use of Intrauterine Contraception Among Women With Employer-sponsored Insurance

Abstract: Rates of IUD use are low among privately insured women in the United States, and higher cost-sharing is associated with lower rates of IUD use. Together with other measures to promote LARC use, eliminating co-pays for contraception could promote the use of these more effective and cost-effective methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…18,19 As a whole, the program has observed a steady increase in IUD and implant provision. 20 Our findings demonstrate that 42% of the California practices that provide IUDs can offer same-day placement, which is substantially higher than the 7% reported in 2006 among a similar sample 14 and higher than the 13% reported more recently among a national sample of obstetrician-gynecologists, 12 suggesting improvements in health care provider capacity.…”
Section: Discussionmentioning
confidence: 94%
“…18,19 As a whole, the program has observed a steady increase in IUD and implant provision. 20 Our findings demonstrate that 42% of the California practices that provide IUDs can offer same-day placement, which is substantially higher than the 7% reported in 2006 among a similar sample 14 and higher than the 13% reported more recently among a national sample of obstetrician-gynecologists, 12 suggesting improvements in health care provider capacity.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, our previous work demonstrated that lower out-of-pocket costs are associated with an increase in IUD use among commercially insured women. (31) By requiring insurance coverage for long-acting contraceptive methods, women with chronic medical conditions may have improved access to safe, highly effective methods. Further research on the impact of the ACA on women’s health should include an assessment of its effects on the delivery of all preventive women’s health services, including contraceptive services.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among women seeking abortion services, 24% reported the cost of contraception as the reason they did not use a method to prevent pregnancy 92. Another study demonstrated that among women with employer-sponsored health insurance, rates of IUD initiation were higher when cost-sharing was lower, even after accounting for cost-sharing levels of other contraceptive methods 93. These studies are concordant showing that when cost is removed, women are more likely to use long-acting options such as IUDs for contraception.…”
Section: Specific Considerationsmentioning
confidence: 99%